Synthetic Biology : New Pathway, New Drug Threat? - Gunasekaran, Nandhakumar (2018)
Synthetic biology is an emerging field in science and technology that can make a positive impact in numerous areas. There are also concerns that it could be misused to exacerbate the illicit drug threat. Authorities worldwide need to nip this potential threat in the bud.